2010
DOI: 10.1017/s0007114510000073
|View full text |Cite
|
Sign up to set email alerts
|

High processed meat consumption is a risk factor of type 2 diabetes in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention study

Abstract: Relatively small lifestyle modifications related to weight reduction, physical activity and diet has been shown to decrease the risk of type 2 diabetes. Connected with diet, low consumption of meat has been suggested as a protective factor of diabetes. The aim was to examine the association between the consumption of total meat or the specific types of meat and risk of type 2 diabetes. The ATBC cohort included middle aged male smokers. During up to 12 years of follow-up, 1098 incident cases of diabetes were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 30 publications
4
32
0
2
Order By: Relevance
“…In a study aimed to examine the association between meat consumption and risk of type 2 diabetes in a large cohort of Finnish middle-aged male smokers [9], over 1,000 incident cases of diabetes were identified in 12 years of follow-up. High total and processed meat consumption emerged as risk factors for type 2 diabetes with 50% and 37% increased adjusted risks, respectively, in the highest vs the lowest quintiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study aimed to examine the association between meat consumption and risk of type 2 diabetes in a large cohort of Finnish middle-aged male smokers [9], over 1,000 incident cases of diabetes were identified in 12 years of follow-up. High total and processed meat consumption emerged as risk factors for type 2 diabetes with 50% and 37% increased adjusted risks, respectively, in the highest vs the lowest quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have been conducted in European countries confirming the association between meat consumption and risk of type 2 diabetes in European populations [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 92%
“…25 A lowsodium diet has also been found to decrease oxidative stress and to improve vascular function in salt-sensitive individuals, 26 and a high sodium intake may promote vascular stiffness. 27 Several prospective studies have observed a positive association between processed meat consumption and risk of type 2 diabetes, 4,28,29 which is a risk factor for cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The Alpha-Tocopherol, Betacarotene Cancer Prevention study of 24,845 participants with 1098 incident cases of diabetes during 12 years of follow-up [41] found a relative risk (RR) of 1.37 (95% CI 1.11-1.71, P = 0.001) for 139 g of processed meat per day compared with 28 g per day in a multivariate model. This association was markedly attenuated by an adjustment for sodium (RR 1.19; 95% CI 0.95-1.49, P = 0 · 10).…”
Section: Sodiummentioning
confidence: 99%
“…This association was markedly attenuated by an adjustment for sodium (RR 1.19; 95% CI 0.95-1.49, P = 0 · 10). This finding led the authors to conclude that the sodium content of processed meat increased the risk of T2DM more than SFA, protein, cholesterol, heme Fe, Mg and nitrate [41]. Processed meat was found to contain on average of 400 % more sodium than unprocessed red meats in the USA [12].…”
Section: Sodiummentioning
confidence: 99%